Low-Latency Web APIs in High-Transaction Systems: Design and Benchmarking - Sravanthi Valiveti, Sesha Sai (International Journal of Computational and Experimental Science and Engineering, 2025)
In the age of digital immediacy, where user experience hinges on speed and responsiveness, the performance of web APIs can significantly affect an organization’s ability to scale and retain users. Particularly in high-transaction systems such as e-commerce, fintech, and online gaming, a few milliseconds of delay can compound into large-scale inefficiencies and lost revenue. This paper presents a comprehensive framework for building, optimizing, and benchmarking low-latency APIs designed to withstand the demands of high-frequency operations. By exploring architectural decisions, async paradigms, caching strategies, and detailed performance metrics, we provide technical guidance and practical results for engineering teams aiming to deliver resilient, real-time web services.